Metazoan parasites of Micropterus salmoides (Centrarchidae: Perciformes) from reservoirs of Nuevo León, México and their association with condition factor and gender - Galaviz Silva, Lucio (2016)
The largemouth bass Micropterus salmoides is a very valuable fish species for aquaculture and sport fishing; however, there are no systematic studies on fish metazoan parasites in Mexico. The main objective of the present study was to describe the prevalence, abundance, and intensity of M. salmoides metazoan parasites, and their association with fish condition factor and gender. The sample size was composed by 672 hosts, collected between 2011-2013 from the following reservoirs of Nuevo Leon, México: Rodrigo Gómez dam (“La Boca”, LB), Cuchillo-Solidaridad dam (CS), Salinillas lagoon (LS), Mariano Escobedo dam (“Sombreretillo”, S), and José López Portillo dam (“Cerro Prieto”, CP). Living fish were transported to the laboratory; sizes and weights were then recorded to calculate the Fulton condition factor (k). If possible, gender was also recorded. Parasites were detected under stereoscopy, recollected and preserved by traditional techniques. Statistical analysis of association between parasitic load, gender, and Fulton condition factor were calculated, using the X2 and the Student-t tests. Results showed that 12 different metazoans were identified, two flukes (Posthodiplostomum minimum centrarchi and Phyllodistomum pearsei), one tapeworm (Proteocephalus ambloplitis), three roundworms (Contracaecum sp., Spinitectus carolini and Philometra nodulosa), two acantocephalan (Neoechinorhynchus cylindratus and Arhythmorhynchus sp.), one leech (Myzobdella moorei), and three copepods (Ergasilus versicolor; Ergasilus arthrosis and Ergasilus cerastes). HSD Tukey test showed that infected fish from LB were significantly different than LS, CS, CP, and S (P<0.05). Parasites most commonly collected in all five locations were P. m. centrarchi, Contracaecum sp. and E. versicolor. The frequency of P. m. centrarchi was highly significant (P<0.001) than other parasites; furthermore, this parasite showed the highest prevalence (97.5 %), abundance (10.12-83.6), and intensity (15.44-88.5). Statistical dependence was found between intensity and abundance of metazoans with regard to female gender and size on five reservoirs (t=143.82, P=0.0001; t=2.6, P=0.01, respectively). In addition, the abundance and intensity showed statistical dependence with regard to k, which was proportionally significant. New locality records for Nuevo Leon include P. m. centrarchi, P. pearsei, P. ambloplitis, Contracaecum sp., Arhythmorhynchus sp., and E. cerastes. Furthermore, P. nodulosa, S. carolini, N. cylindratus, and E. arthrosis were new records for Mexico.